Techno-Economic feasibility of enhanced geothermal systems (EGS) with partially bridging Multi-Stage fractures for district heating applications. (1st April 2022) - Yu, Pengliang; Dempsey, David; Archer, Rosalind
Highlights: We introduce a simulation framework to assess the techno-economic feasibility of EGS district heating using a partially-bridging multi-fracture design. Stimulated permeability, reservoir temperature, and fracture number are essential for maximising constant stable thermal power output. Applied to the Qiabuqia EGS field, China, we show that a 14-fracture EGS is economically viable, heating greater than 28 000 dwellings over 20 years with emissions reduction of 1.5 Mt CO2 . Abstract: Here, we investigate the techno-economic feasibility of an enhanced geothermal system (EGS) for direct heating, using a new horizontal-well with partially-bridging fractures design. To do this, we developed numerical models to evaluate reservoir dynamics and output, economic performance and environmental benefits. This model was used to determine optimal thermal power output over a 20-year operation for given parameters. Then, we ranked the effects of key parameters on commercial and environmental outcomes. Stimulated reservoir permeability and reservoir temperature are the primary determinants of economic viability, with lesser effects due to reservoir depth and fracture number. A case study was developed for the Qiabuqia EGS, China, capturing uncertainty through sampling of a surrogate model. We show that a 14-fracture design was economically preferred, providing up to 2.8 km 2 of indoor heating over 20 years with considerable emissions offset (∼1.5 Mt of CO2 ) and economic benefit (24–185 M$).